Life Skill Education Management of Islamic Boarding Schools in Metro City - Saerah; Juhri Abdul Muin; Jamal Fakhri; Muhammad Akmansyah (Prodi Manajemen Pendidikan Islam Universitas KH Chalim Mojokerto, 2024)
This research examines the implementation of life skills education management in three Islamic boarding schools in Metro City, namely Darul A'mal Islamic Boarding School, Tuma'ninah Yasin Islamic Boarding School, and Daarul Ulya Islamic Boarding School. A qualitative descriptive approach was used with data collection techniques through interviews, observation and documentation. The research results show that the three Islamic boarding schools have implemented life skills education management through the stages of planning, organizing, implementing and supervising. Planning is carried out comprehensively by involving various parties and considering environmental analysis. Organizing includes dividing tasks according to expertise, coordination, and providing facilities and infrastructure. Implementation includes various skills with varied learning methods and active participation of students. Supervision is carried out periodically through evaluation to ensure the success of the program. However, there are limitations in generalizing research results, exploring the impact of life skills education, and using quantitative methods. This research contributes to the development of educational management science, especially in the application of life skills education in Islamic boarding schools.